Xogo popular galego e educación : Vixencia educativa e función de identificación cultural dos xogos e enredos tradicionais - Veiga García, Francisco Manuel (1998)
"This reserch is divided into 4 parts. The first, which deals with the theoretical basis of game itself, develops such matters as the concept of game, explanatory theories, different stages in the evolution of games and their educative use. The second is also theoretically based, like the first part, and holds the same structure, as it deals with the same aspects, focused now on popular and traditional games. In the third part, a descriptive, educative analysis of a set of 123 popular, traditional games is carried out; it tries to find out their educative potentials and their application in teaching strategies nowadays. The choice of these games has been made taking into account 2 criteria: the different stages in the player's life -from early childhood to old age-, and the variety of games in the catalogue of popular and traditional games. These 2 criteria are connected with a classification of Galician popular games which organizes these according to the different stages in the evolution of the human being. In the fourth and last part, a research based on a questionaire answered by representatives of 320 primary schools all over Galicia, tries to find out the present use of these popular games in the Galician Education system, as well as the interest that teachers show for them. Among the most outstanding conclusions of this research we must mention that the popular games of this catalogue that need/develop physical skills, as well as those symbolic games that reflect the social structure, values, fears... of the traditional Galician society, are more practised. Besides, all the games perfectly integrate the individual into his/her surroundings and environment, fact which we consider very important from an educative point of view. There seems to be an increasing interest for this pedagogical resort in schools, although there's more improvisation than a carefully planned -and so, more ambitious- programme of activities related to traditional games and their use in education."